Qualitative and Quantitative NAD+ Metabolomics Lead to Discovery of Multiple Functional Nicotinate N-Glycosyltransferase in Arabidopsis - Liu, Lingyun; Zhang, Fengxia; Li, Guosheng; Wang, Guodong (Frontiers in Plant Science, 2019)
The Preiss-Handler pathway, which salvages nicotinate (NA) for NAD synthesis, is a conserved biochemical pathway in land plants. We previously demonstrated that various NA conjugations (mainly methylation and glycosylation) shared the NA detoxification function in all tested plants. It remains unclear whether other NA conjugates with low abundance exist in plants. In this study, we discovered at least two additional NA N-glycosides in Arabidopsis, which was tentatively elucidated as nicotinate N-pentoside (NaNP) and NA N-rhamoside (NaNRha), using liquid chromatography triple-quadrupole mass spectrometry (LC-QQQ-MS) with precursor ion-scanning (PreIS). We further quantitatively profile the NAD+-related metabolites in 24 tissues of Arabidopsis. Biochemical assays of UGT76C family revealed that UGT76C5 (encoded by At5g05890, previously identified as NaNGT) was a multiple functional nicotinate N-glycosyltransferase, with high preference to UDP-xylose and UDP-arabinose. The deficiency of NaNP and NaNRha in ugt76c5 mutant suggested that UGT76C5 is responsible for biosynthesis of NaNP and NaNRha in planta. We also identify one amino acid difference in (Plant Secondary Product Glycosyltransferase) PSPG motif is responsible for the divergence of NaNGT (UGT76C4) and UGT76C5. Taken together, our study not only identifies a novel nicotinate N-glycosyltransferase but also paves the way for investigations of the in planta physiological functions of various NA conjugations.